1996
DOI: 10.1113/jphysiol.1996.sp021530
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying orientation selectivity of neurons in the primary visual cortex of the macaque.

Abstract: 1. Effects of blocking intracortical inhibition by microiontophoretic administration of bicuculline methiodide (BMI), a selective antagonist for GABAA receptors, on orientation selectivity of 109 neurones were studied in the primary visual cortex (V1) of anaesthetized and paralysed monkeys. 2. The averaged orientation tuning of visual responses of cells was poor in cytochrome oxidaserich blobs of layer II/III and in layer IVc/J, moderate in layers IVb, IVca and V, and sharp in the interblob region of layer II/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
108
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 39 publications
12
108
1
Order By: Relevance
“…This is also consistent with evidence that blocking inhibitory effects across a local population of cortical cells greatly reduces orientation selectivity (Sillito, 1975;Tsumoto et al, 1979;Sato et al, 1996). In the model, blockade of inhibition from neurons with a specific orientation preference should cause neighboring prediction neurons to show increased response to that orientation, rather than simply causing a general disinhibition to all orientations.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…This is also consistent with evidence that blocking inhibitory effects across a local population of cortical cells greatly reduces orientation selectivity (Sillito, 1975;Tsumoto et al, 1979;Sato et al, 1996). In the model, blockade of inhibition from neurons with a specific orientation preference should cause neighboring prediction neurons to show increased response to that orientation, rather than simply causing a general disinhibition to all orientations.…”
supporting
confidence: 74%
“…Such effects have been recorded in V1 (Crook et al, 1998), and analogous data have been obtained from cortical area TE (Wang et al, 2000). The current model is also consistent with neurophysiological evidence that the strength of lateral inhibition peaks for stimuli presented at the preferred orientation of the recorded cortical cell (Ferster, 1986;Sato et al, 1996;Sompolinsky and Shapley, 1997). In the model, the strength of inhibition between any two prediction neurons is proportional to the degree of overlap between the RFs.…”
supporting
confidence: 66%
“…There is also evidence that the influence of inhibition on orientation tuning in monkey V1 depends strongly on layer. Sato et al [57] found that the broadening of orientation tuning that results from local iontophoresis of GABA antagonists was strongest outside of the input layers. Thus, orientation tuning may be re-computed in different cortical layers, by use of different synaptic integration mechanisms.…”
Section: Diversity In Subthreshold Tuningmentioning
confidence: 99%
“…However, feedforward excitation alone cannot provide the suppression of responses to nonpreferred orientations that has been observed (De Valois et al, 1982;Celebrini et al, 1993;Ringach et al, 2002b). To account for orientation selectivity, theorists have proposed corticocortical amplification (Ben-Yishai et al, 1995;Somers et al, 1995;Mariño et al, 2005), corticocortical inhibition (Sato et al, 1996;Troyer et al, 1998;McLaughlin et al, 2000;Monier et al, 2003), and presynaptic depression Freeman et al, 2002). Many experimental studies (Nelson and Frost, 1978;Sillito et al, 1980;Bonds, 1989;Volgushev et al, 1993;Sato et al, 1996;Ringach et al, 2002a,b;Shapley et al, 2003) concluded that suppressive or inhibitory cortical mechanisms were involved.…”
Section: Neuronal Processes Involved In Orientation Selectivitymentioning
confidence: 99%